2000
DOI: 10.1002/chin.200038226
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Exotic Amino Acids. Part 1. Synthesis of α‐Amino Acids with a Cyclohexene Substituent.

Abstract: Exotic Amino Acids. Part 1. Synthesis of α-Amino Acids with a Cyclohexene Substituent.-A new method for the preparation of the exotic, i.e unnatural, title amino acids (VI) (6 examples) from ylidene derivatives of Meldrum acid (I) using a cycloaddition-amination-Hofmann rearrangement strategy is developed. -(ZITSANE, D. R.; RAVINYA, I. T.; RIIKURE, I. A.; TETERE, Z. F.; GUDRINIETSE, E. YU.; KALEI, U. O.; Russ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[10] The domino Knoevenagel/ Diels-Alder reaction would then generate a quaternary center with formation of three new carbon-carbon s bonds through amino acid catalysis. This proposal was reflective of the pioneering studies of Tietze and Beifuss [11a,b] and our recent disclosure of the first direct asymmetric Knoevenagel/ Michael reactions with ketones, aldehydes, and malonates involving alkylidene malonates generated under organocatalysis that subsequently react as electrophiles with ketonederived enamines also generated under organocatalysis. [3a] In contrast to this early study where asymmetric induction was compromised by the use of the cyclic malonate Meldrum's acid, the alkylidene derivative of Meldrum's acid proved to be more efficient in the Diels-Alder reaction than the alkylidene formed from alkyl malonates.…”
mentioning
confidence: 86%
“…[10] The domino Knoevenagel/ Diels-Alder reaction would then generate a quaternary center with formation of three new carbon-carbon s bonds through amino acid catalysis. This proposal was reflective of the pioneering studies of Tietze and Beifuss [11a,b] and our recent disclosure of the first direct asymmetric Knoevenagel/ Michael reactions with ketones, aldehydes, and malonates involving alkylidene malonates generated under organocatalysis that subsequently react as electrophiles with ketonederived enamines also generated under organocatalysis. [3a] In contrast to this early study where asymmetric induction was compromised by the use of the cyclic malonate Meldrum's acid, the alkylidene derivative of Meldrum's acid proved to be more efficient in the Diels-Alder reaction than the alkylidene formed from alkyl malonates.…”
mentioning
confidence: 86%
“…A suspension of the monohydrazide of 2-phenylcyclohexene-1,1-dicarboxylic acid (14) (0.3 g, 1.0 mmol) [7] and isatoic anhydride (15) (0.167 g, 1.0 mmol) in triethyl orthoformate 2 (3 ml) was boiled for 5 h. The excess of the ortho ester was distilled, and the residue was recrystallized from hexane. We obtained 0.12 g (48%) of compound 16, which according to the analytical and spectral data was similar to the compound obtained in [9] from the anhydride 14 and triethyl orthoformate 2.…”
Section: -[1-hydroxycarbonyl-4-methyl-2-(4-r-phenyl)-4-cyclohexen-1-mentioning
confidence: 99%
“…3 Me, 5, 9, 13 R 1 = Ph; 6-9 R 2 = COOH, 10-13 R 2 = H __________________________________________________________________________________________ These reactions are attractive in that the C-2 atom of the quinazoline ring can be modified depending on the structure of the orthoester, and the C-1 atom of the cyclohexene can be modified depending on the reaction conditions. We established that the N′-cyclohexenecarbonylhydrazides 1a,b, which we synthesized [1] from the monohydrazides of 2-arylcyclohexene-1,1-dicarboxylic acid [7] and isatoic anhydride 15, react with orthoformic (2) and orthoacetic (3) triethyl esters and also with orthovaleric (4) and orthobenzoic (5) methyl esters even at room temperature. The respective 3-cyclohexenylamido-2-R 1 -quinazolin-4-ones 6-9 are formed with high yields.…”
mentioning
confidence: 99%
“…We were interested in the synthesis of hexahydro-1-benzothiophene S,S-dioxide derivatives from the corresponding hexahydrospiro[1-benzothiophene-4,5′-[1,3]-dioxane]-4′,6′-dione 1,1-dioxides [10] via opening of the 1,3-dioxane ring [11,12]. We previously showed that the 1,3-dioxane ring in spiro adduct VIII is readily cleaved by the action of ammonia in dioxane or potassium hydroxide in methanol.…”
mentioning
confidence: 99%